Diversity Species and Dominance of Gastropods on Lantebung Mangrove Ecosystem, City of Makassar - Janwar, Zul; Ahmad, Amran; Soma, Andang Suryana (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
The Lantebung mangrove ecosystem in Makassar City is one of the mangrove ecosystems in Makassar City, which has been used by the community as a mangrove tourism area. The purpose of this study was to determine the level of species diversity and the dominate of gastropod species in the Lantebung Mangrove ecosystem, Makassar City. This research is an exploratory descriptive research. Determination of stations is done by purposive sampling with 3 research stations. Where is every station. At each station a 20 meter long transact was made with 5 subplots measuring 1m x 1m. The results of this study indicated that the index of gastropod diversity in the Lantebung mangrove ecosystem, Makassar City is in the medium class with a value of 1.235. The Dominance Index found that the Dominance of Gastropod Species was in the low class with a value of 0.388.